Differences in Stress and Anxiety Among Women With and Without Children in the Household During the Early Months of the COVID-19 Pandemic - Avery, Ally R.; Tsang, Siny; Seto, Edmund Y. W.; Duncan, Glen E. (Frontiers in Public Health, 2021)
The COVID-19 pandemic and resulting lockdowns have had a disproportionate impact on parents of children under 18, particularly women. Mandatory school closures and loss of childcare resulted in parents balancing work, teaching, and childcare needs. A number of studies have examined changes in mental health of parents, but to date no studies have compared the differences in stress and anxiety levels between women with and without children in the United States. Adult women from the Washington State Twin Registry (WSTR) (N = 1,014, pair N = 529) and mothers of twin children enrolled in the WSTR (N = 147) completed an online survey examining several health-related behaviors and outcomes and their self-reported changes due to COVID-19. We conducted two studies to examine the impact of children on stress and anxiety levels among women. In study 1, we assessed whether women living in households with children under the age of 18 have higher levels of stress and anxiety than those without children in their household. We found that perceived stress levels did not differ between women with and without children in the household, but anxiety levels were higher among women living with children than those without. In study 2, we assessed whether the correlation between children in the household and stress/anxiety is accounted for by non-random genetic and environmental selection effects, causal processes, or both using a sample of adult female twins. We found that the presence of children in the household was associated with higher levels of stress and anxiety. However, this association is confounded by genetic and shared environmental factors. Our findings highlight the need to provide supporting resources to women living with children in the household during and after the COVID-19 pandemic.